Analysis of the Issue of Affirmative Action on Domestic Violence in Islam: A Study of Surah An-Nisa' Verses 34, 35 and 128 - Alvian Bhakti Pamungkas; Nabila Thyra Janitra (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2025)
Along with the massive issue of Domestic Violence (DV), Islam as a religion that focus on peace and elevates the status of women actually gets a distorted understanding, namely affirmation of domestic violence, precisely in Surah An-Nisa verse 34, 35 and 128 which is only understood textually where the husband is allowed to separate the bed and beat his wife. So, it is necessary to conduct an in-depth study of the verse to analyze the issue of affirmation of domestic violence in Islam. This study was conducted with a literature study through sources relevant to the topic. Through this research, it was found that Islam has never affirmed the existence of domestic violence. Through the study of tafsir and asbabun nuzul of the verse concerned, Islam states that men have the right to lead the family and wives are obliged to obey their husbands in matters justified by religion. The husband's advantage over the wife should not be abused to commit violence against the wife. The verse explains the solutionthat are presented in the event of nusyuz between the two in different and detailed ways. These methods are also relevant to the psychological conditions of women and men, so the statement that Islam justifies domestic violence is an unjustified statement.